The transformation of water and sewage management in Poland and Ukraine in the light of socio-economic and political conditions - Piasecki, Adam (Bulletin of Geography. Socio-economic Series, 2022)
The study aims to evaluate and compare the transformations in water and sewage management that have taken place in Poland and Ukraine since the early 1990s. This required the collection of an appropriate dataset. Due to differences in reporting methods between countries, it was decided to select only those variables and indicators that allowed for a comparative analysis. The analysis indicated significant and positive changes in the scope of water and sewage management in both countries. Much greater progress was seen in Poland, where, mainly thanks to EU funding, the costly water and sewage infrastructure was more quickly modernised and expanded. However, it is also emphasised that areas related to water and sewage management in Poland still require improvement. In the case of Ukraine, it is indicated that measures should be aimed most urgently at reducing the quantity of untreated sewage discharged into waters and soils and to increasing wastewater treatment standards (including nutrient reduction, in particular). It is also extremely important to introduce in law – and ensure the effective enforcement of – appropriate environmental protection regulations.